Implementation of Mubādalah in Households: A Study of the Fulfillment of the Rights and Obligations of Contemporary Husband and Wife - Agus Hermanto; Rochmad Rochmad; Mahmudin Bunyamin; Siti Nurjanah; Agus Setiawan (Journal of Islamic Mubadalah, 2024)
Men are heads of households and wives are housewives. That is the paradigm embedded in our society in general, because so far men have always been the main ones in the front line while wives have always been in a limited area, the problem is that contextually, the role of women is no longer in the domestic area alone, but many have also played a role outside the home to help their husbands earn a living. The question in this article is how can the rights and obligations of husband and wife be carried out in this context? The purpose of this research is to obtain a reconstruction of new rights and obligations that are based on fikih mubadalah. This research is a literature research study, qualitative analysis approach with analysis of mubadalah theory, primary data sources obtained from several documents related to this study. The result of this study is that partners between men and women in realizing justice in the household must be equal, such as mutual deliberation, mutual realization of democracy and mutual good deeds in relationships. The contribution of this article can be applied in households to achieve a harmonious and prosperous household.